The Necessity of Designing Assessment Tool of Multimedia in Health Interventions: A Viewpoint - Zohre Rahaei; Saeide Rastjoo (Gonabad University of Medical Sciences, 2024)
Any health strategy aims to improve people's health level and quality of life with special emphasis on the development of health education. Health system workers must have sufficient knowledge and skills in designing, implementing, and assessing health education programs. One of the critical points in educational planning is the selection of the most suitable educational methods and media to convey the content of the education to the audience to lead to the desired learning of the learners.